Dilemma of Unregistered Marriage for Establishing Children's Lineage - Aples, Aples; Mardianton, Mardianton; Rahmita, Rahmita; Kapitri, Neneng; Nurlaila, Nurlaila; Yusrizal, Syamsi (Samara: Journal of Islamic Law and Family Studies, 2024)
The petitioner filed a request for the determination of lineage to ensure the child's rights are fulfilled. Based on legal considerations, the Judge granted the request by considering the evidence presented, such as letters and witness testimonies. Legal facts indicate that the children were born from the lawful marriage of Petitioner I and II, thus they are eligible to be recognized as legitimate children. This chapter discusses the research findings and discussion regarding the background of the implementation of marriage reformation/tajdid nikah and the submission of requests for the determination of child's lineage in case No. 115/Pdt.P/2023/PA.PN at the Religious Court of Painan. The research method used by the researcher is a legal approach (state approach) with descriptive-analytical specifications in the case decision: 115/Pdt.P/2023/PA.PN. Results. Firstly, the reformation of marriage in Case 115/Pdt.P/2023/PA.PN is based on reasons that align with religious and governmental regulations, such as the previous marriage being terminated due to the waiting period (iddah), for administrative validity, and the marriage being conducted solely for the official record from the Office of Religious Affairs (KUA). Secondly, the background of the submission of the request for the determination of child's lineage is because Petitioner I and II had a secret marriage in 2015, were blessed with 2 children, their effort for formalizing the marriage was rejected, then they officially registered their marriage in 2023. The aim is to ensure the fulfillment of the children's rights such as birth certificates and education. Thirdly, in deciding the case of the child's lineage, the judge's consideration is based on juridical, philosophical, and sociological aspects, taking into account the fulfillment of the rights and welfare of the child.